Students’ Learning Styles in English Classes in Inclusive Schools - Meinawati, Euis; Sabian, Annaba Tama; Jimmi; Sulistyawati, Meiva Eka Sri; Suwarsito (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
Learning in an inclusive environment has numerous advantages. Still, it also presents several challenges that must be addressed, such as accommodating the diverse learning styles of both regular students and those with special needs. This study aims to determine the learning styles of students learning English in an inclusive learning environment and to explore the match between students' learning styles and teachers' teaching styles within this environment. The sample was Champions Community Homeschooling students who completed the form and responded to the questionnaire. They were divided into ten regular students and five students with special needs. This study was conducted at Champions Community Homeschooling, which is an inclusive school. This Champions Community Homeschooling inclusive school is located in Bogor, West Java, Indonesia. The study took place from March to September 2024. This study employed a qualitative approach, utilizing a case study method. Data were collected using observations of the teaching and learning process and questionnaires. Data analysis techniques included data reduction, data presentation, and conclusion. The study found that the learning style that dominated special needs students in English classes was the aural learning style, followed by the reading/writing learning style. However, regular students had a reading and writing learning style, followed by a visual learning style. The results of this study also have implications for educators to design more flexible and inclusive teaching strategies that accommodate diverse learning styles.